Not one, but many "publics": public engagement with global development in France, Germany, Great Britain, and the United States. Issue 6 (17th August 2020) - Hudson, Jennifer; Hudson, David; Morini, Paolo; Clarke, Harold; Stewart, Marianne C.
ABSTRACT: Using new panel data from the Aid Attitudes Tracker (2013–18), this article draws on a set of 18 actions to map public engagement with global poverty in France, Germany, Great Britain and the United States. It introduces a new engagement segmentation comprised of five distinct groups – the totally disengaged, marginally engaged, informationally engaged, behaviourally engaged, and fully engaged. The data provide evidence of both aggregate and individual-level change in engagement over time but with an important distinction: respondents in less engaged groups are less likely to move out of these groups and tend to stay unengaged. Respondents in more engaged groups are more likely to move in and out of engagement.